Fabrication of wavelength division multiplexed in-fibre Bragg grating arrays for structural monitoring applications - Dockney, Michael Lee (Cranfield University, 1997)
Wavelength division multiplexed arrays of in-fibre Bragg gratings (IFBGs) are fabricated in hydrogen loaded optical fibres. The IFBG arrays are embedded into a carbon fibre composite test beam for the purpose of quantitative dc strain sensing. A near-field phase mask writing technique is compared to a conventional mirror interferometer and a novel phase mask based interferometer writing scheme. The combination of a wavelength tuneable UV source and a phase mask based interferometer offers, either a large spectral coverage of 51nm, or a laser limited Bragg wavelength accuracy of 0.03nm in the 800nm spectral region. The characteristics of gratings fabricated using these schemes are discussed. The axial strain sensitivity of optical fibre is investigated in a preliminary experiment. A three point bend test is then used to compare the theoretical strain applied to a carbon fibre test beam with measurements made by electrical strain gauges and embedded IFBG sensors over the range ±3400pstrain. A residual tensile strain results from embedding and is generally measured to be >2000pstrain. The majority of IFBG sensors appear well bonded to the surrounding host material and, with one exception, the strain responses of uncoated IFBG sensors deviate from the theoretically predicted values by <4.3%. A buffer coat around the sensor reduces the strain response by ~4% but does not affect its linearity or reproducibility. A spliced IFBG pair is used to separate strain and temperature measureands. A transfer matrix for the scheme is experimentally determined that has a calculated condition number of 23. The technique is compared to other reported methods of strain and temperature separation. Also, a demodulation scheme for IFBG sensors based on a volume holographic filter formed in photorefractive BaTi03 is reported. The filter has a strain measurement range of 2500pstrain, with a minimum detectable strain of 4pstrain/VHz.